Group counseling with values clarification techniques to increase students' respect - Gunawan, I Made Sonny; Gunawan, Made; Huda, Khairul (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Individuals must own respect because it can be an internal controller in making logical decisions to behave by moral values. This study aimed to confirm the effectiveness of the values clarification group counselling on respect. This study used a repeated measure experimental design. The subjects in this study were 10 students at SMK Negeri 2 Mataram who indicated having a low category of respect. Data were collected using a respectful attitude questionnaire. Data analysis used repeated measure statistics ANOVA. The results of this study indicate that values clarification group counselling is effective in increasing student respect. Students' understanding regarding respect is inseparable from how to create good relationships between students and teachers as a form of creating a healthy and conducive school climate.